2003
DOI: 10.1074/jbc.m211492200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Glycosyltransferases Synthesizing Major Bilayer and Nonbilayer-prone Membrane Lipids inAcholeplasma laidlawii and Streptococcus pneumoniae

Abstract: In membranes of Acholeplasma laidlawii two consecutively acting glucosyltransferases, the (i) ␣-monoglucosyldiacylglycerol (MGlcDAG) synthase (alMGS) (EC 2.4.1.157) and the (ii) ␣-diglucosyl-DAG (DGlcDAG) synthase (alDGS) (EC 2.4.1.208), are involved in maintaining (i) a certain anionic lipid surface charge density and (ii) constant nonbilayer/bilayer conditions (curvature packing stress), respectively. Cloning of the alDGS gene revealed related uncharacterized sequence analogs especially in several Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 63 publications
3
62
0
Order By: Relevance
“…This protein has higher similarity to the plant-type MGDG synthase than to cyanobacterial MGlcDG synthase even though the protein transfers Glc to acceptors. However, by using cyanobacteria, it was shown that the enzyme catalyzes transfer of Glc to MGDG rather than to DAG in vivo, similar to diglucosyldiacylglycerol synthase of A. laidlawii (Edman et al, 2003). Thus, the enzyme is a diglycosyldiacylglycerol synthase, probably not an MGlcDG synthase.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has higher similarity to the plant-type MGDG synthase than to cyanobacterial MGlcDG synthase even though the protein transfers Glc to acceptors. However, by using cyanobacteria, it was shown that the enzyme catalyzes transfer of Glc to MGDG rather than to DAG in vivo, similar to diglucosyldiacylglycerol synthase of A. laidlawii (Edman et al, 2003). Thus, the enzyme is a diglycosyldiacylglycerol synthase, probably not an MGlcDG synthase.…”
Section: Discussionmentioning
confidence: 99%
“…1). For this purpose, glycosyltransferases were selected from bacterial origin that had previously been characterized by heterologous expression in prokaryotic or eukaryotic hosts (Escherichia coli, Pichia pastoris, Saccharomyces cerevisiae, and Synechococcus) and subsequent analysis of newly formed glycolipids (20)(21)(22)(23)(24)(25)(26). Additional putative glycosyltransferases were identified in bacteria based on sequence similarity to known genes (Table 1) (26), and by this 20 bacterial genes were selected for expression in plants.…”
Section: Resultsmentioning
confidence: 99%
“…The best studied glycosyltransferases include the MGD/MGlcD and DGD synthases from plants and cyanobacteria (15)(16)(17)(18), the MGlcD and DGlcD synthases from Acholeplasma (7,19), and the processive glycosyltransferases from the Gram-positive bacteria Staphylococcus or Bacillus (20,21). There are only a few glycosyltransferases characterized as promiscuous enzymes, such as Pgt from Agrobacterium or Mesorhizobium, or the processive glycosyltransferases from the human pathogens Mycoplasma pneumoniae and Mycoplasma genitalum using UDP-Glc and UDP-galactose (UDP-Gal) as sugar donors (11,22,23).…”
Section: Discussionmentioning
confidence: 99%